Non-college Occupations, Workplace Routinization, and the Gender Gap in College Enrollment - Amanda Chuan; Weilong Zhang (Institute of Labor Economics (IZA), 2023)
This paper explores how non-college occupations contributed to the gender gap in college enrollment, where women overtook men in college-going. Using instrumental variation from routinization, we show that the decline of routine-intensive occupations displaced the non-college occupations of women, raising female enrollment. Embedding this instrumental variation into a dynamic Roy model, we find that routinization decreased returns to the non-college occupations of women, increasing their college premium. In contrast, men's non-college occupations were less susceptible to routinization. Our model estimates that workplace routinization accounted for 44% of the growth in female enrollment during 1980-2000.
Keywords: I23; I24; I26; J16; J24; J23; 330; gender; college enrollment; human capital; occupations; automation